GCT-08. Patients with Metastatic Central Nervous System Germinoma Involving the Basal Ganglia and Thalami, a Case Series. (3rd June 2022) - Abu-Arja, Mohammad; Graham, Richard; Cappellano, Andrea; Finlay, Jonathan; Gajjar, Ammar; Lucas, John; Tinkle, Christopher; Allen, Jeffrey; Abdelbaki, Mohamed
Abstract: BACKGROUND: Central nervous system (CNS) germinomas are commonly located in the suprasellar and/or pineal regions. Current treatment strategies include irradiation (RT) alone or chemotherapy with RT to reduce the dose and field of RT. However, given their rarity and poorly defined imaging characteristics, germinomas originating in the basal ganglia/thalami (BGTG) have proven challenging to treat. We present a case series of six patients with metastatic BGTG, given the paucity of published research on patients with metastatic CNS BGTG. METHODS: A retrospective multi-institutional review was performed across four institutions in two countries. RESULTS: Two patients were females, and four were males. The median age at presentation was 14.9 years. Biopsies were performed in all patients except for one patient who underwent subtotal surgical resection of her primary tumor. Three patients received RT only, while the remaining three received chemotherapy with RT. Carboplatin and etoposide were used in all three patients who received chemotherapy. All six patients received craniospinal irradiation (CSI). For patients who received RT only, the CSI dose ranged between (24 – 27.2 Gy) with a total dose to the primary site ranging between (36 – 40 Gy). For patients who received chemotherapy, one patient received 36 Gy with a total dose of 54 Gy to the primary site. The second patient received 24 Gy with a total dose of 40 Gy to the primary site. The CSI dose was not available for the third patient. All patients remain alive with a median event-free survival (EFS) and overall survival (OS) of 49 months (range: 14.3 – 168 months). CONCLUSION: In our series, patients with metastatic CNS BGTG treated with CSI with or without chemotherapy had excellent outcomes. Future larger studies are needed to compare the outcomes between CSI only and chemotherapy with low-dose CSI among patients with metastatic CNS BGTG.